Tiredness, depression, and sleep disorders in frontline healthcare workers during COVID-19 pandemic in Vietnam: A field hospital study - Duong-Quy, Sy; Tran-Duc, Si; Hoang-Chau-Bao, Dinh; Bui-Diem, Khue; Vu-Tran-Thien, Quan; Nguyen-Nhu, Vinh (Frontiers in Psychiatry, 2022)
Background. The COVID-19 outbreak witnessed in the autumn of 2021 led to unprecedented changes in the Vietnamese health system. Many field-hospitals were built up around the country and health workers have been mobilizing to epidemic areas, including medical students. Methods and Objectives. We measured sleep disorders, depression and fatigue in volunteers working at field-hospitals during that outbreak. It was a cross-sectional study using a self-responsive questionnaire. Sleep characters, including STOP’s elements were questioned. Health worker burnout was detected using Pichot’s questionnaire. Results. 100 frontline health workers (FHW) were included in the study. 86 were female. The mean sleep-time of FHW before, while working and during the isolation period after working at Covid-19 field hospitals were consecutively 7.78±1.48, 5.71±1.40 and 8.78±2.31 hours per day. Burnout was not a crucial issue for these young volunteers. The mean score of Pichot’s Fatigue Scale was 4.18 (SD=5.42). The Pichot’s Depression mean score was 2.54 (SD=3.36). Thirteen of them were suspected of depression. Appropriate work schedule, better sleep conditions and mental health support could be helpful for frontline health workers. The 2 weeks of isolation after working period in field hospitals were very worthwhile, not only to avoid the virus spreading but also for health workers recovering. Conclusion. Identification of protective factors to assure the health personnel’s well-being and to avoid burnout could be a significant weapon, giving us the ability to respond in a better way against the following COVID‐19 waves in the near future.